2001
DOI: 10.1128/iai.69.3.1755-1765.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human Natural Killer Cells Mediate Killing of IntracellularMycobacterium tuberculosisH37Rv via Granule-Independent Mechanisms

Abstract: Despite the continued importance of tuberculosis as a world-wide threat to public health, little is known about the mechanisms used by human lymphocytes to contain and kill the intracellular pathogen Mycobacterium tuberculosis. We previously described an in vitro model of infection of human monocytes (MN) with virulent M. tuberculosis strain H37Rv in which the ability of peripheral blood lymphocytes to limit intracellular growth of the organism could be measured. In the current study, we determined that lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
82
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 45 publications
(31 reference statements)
8
82
0
5
Order By: Relevance
“…Interestingly, these cells show cytolytic activity and are able to produce IFN-␥, which plays a central role in the development of cell-mediated immunity and host immune response against the Mtb (1). The effect of Mtb-induced chemokines on NK cells is consistent with a recent report on the role of NK cell-mediated innate immune response against Mtb (34). Moreover, the chemotaxis of NK cells induced by chemokines released from Mtb-infected DC is of particular interest in light of a new observation suggesting significant cross-talk between NK cells and DC that was required for their reciprocal activation and maturation (35).…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, these cells show cytolytic activity and are able to produce IFN-␥, which plays a central role in the development of cell-mediated immunity and host immune response against the Mtb (1). The effect of Mtb-induced chemokines on NK cells is consistent with a recent report on the role of NK cell-mediated innate immune response against Mtb (34). Moreover, the chemotaxis of NK cells induced by chemokines released from Mtb-infected DC is of particular interest in light of a new observation suggesting significant cross-talk between NK cells and DC that was required for their reciprocal activation and maturation (35).…”
Section: Discussionsupporting
confidence: 74%
“…However, IFN-␥ was not required for cytotoxicity, which was unaffected by addition of anti-IFN-␥ Abs. Similarly, IFN-␥ does not mediate the capacity of NK cells to kill intracellular M. tuberculosis (23). Although IFN-␥ produced by NK cells in response to M. tuberculosis-infected macrophages does not directly mediate cytotoxicity, it may contribute to immune defenses by favoring the development of a protective type 1 response, as IFN-␥ can enhance the production of both IL-12 and IL-18 in response to M. tuberculosis (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Denis (21) first showed that freshly isolated NK cells from healthy donors can lyse M. tuberculosis-infected monocytes and reduce the rate of intracellular bacillary growth, but the mechanisms underlying these effects were not investigated. One study found that growth inhibition was mediated by soluble factors produced by NK cells, whereas another suggested that growth inhibition required contact between NK cells and monocytes and was associated with the induction of monocyte apoptosis (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, in vitro experiments showed that IL-12 release that is of paramount importance for the development of a protective Th1 response is restricted to M. Tb-infected DC, whereas macrophages preferentially produce TNF-␣, IL-1, and IL-6 (21,22). Similarly, the selective secretion of type I IFN by M. Tb infected human DC will stimulate and recruit NK cells (23,24), which are capable of killing intracellular M. Tb (25)(26)(27). However, these in vitro observations may not reflect the net effect of type I IFNs in vivo, because-at least in mice-type I IFNs aggravate the course of tuberculosis (28) and NK cells are not substantially involved in protection (29).…”
Section: Discussionmentioning
confidence: 99%